MULTI-MORBIDITY AND THE PATHWAY TO DISABILITY. (11th November 2018) - Jacob, M; Jor'dan, A; Leritz, E; Bean, J
Abstract: Multimorbidity increases risk for disability, however, the mechanism by which chronic diseases affect function is unclear. We aimed to determine 1) the effect of multimorbidity burden on disability scores over 2 years of follow-up and 2) the proportion of the effect mediated by deterioration in habitual gait speed and cognitive function (measured by Mini Mental Status Exam, Digit Symbol Substitution Test, and Trails B) in a cohort of 430 community living older adults at risk for mobility disability. Multimorbidity was determined from 13 chronic conditions self-reported at baseline and thereby grouped by 0–2, 3–5 or ≥6 chronic conditions. Disability was measured annually using the Late Life Function and Disability Instrument (LLFDI). We utilized mixed models adjusting for confounders (age, sex, race, education, marital status, BMI, pain, physical activity levels) to test the association between multimorbidity burden and repeated measures of LLFDI scores. Participants with a multimorbidity score of ≥6 was associated with significantly lower LLFDI basic lower limb function (-4.9 points), advanced lower limb function (-6.2 points), participation (-5.2 points) and frequency of participation (-2.3 points) scores over 2 years compared to participants with a multimorbidity score of 0–2. Effects were partially attenuated by time-varying gait speed (13 -26%) but not by time-varying MMSE, DSST or Trails B scores. Gait speed decline partially accounts for activity limitations and participation restriction among older adults with high multimorbidity burden. Cognitive decline does not appear to be part of the mechanism.